Vývoj matematického vzdělávání v České republice po roce 1989 - Robová, Jarmila; Moravcová, Vlasta (Scientia in educatione, 2019)
Teaching mathematics at elementary and secondary schools in the Czech Republic has undergone marked changes over the past 30 years. These changes have influenced the education of pupils and their causes have been largely internally driven. At the end of the 1980s and start of the 1990s, we moved away from a set-based concept of mathematics, prompting the publication of new textbooks. Characteristic during the 1990s was a decline in the amount of maths lessons in the curriculum, changes in the concept of the taught content (a move away from exact definitions, reduced emphasis on the use of symbolic notation and the memorising of basic relations, etc.). We also observed in the teaching methods a growing tendency towards constructivism, support for project-based learning, and the introduction on a mass scale of digital technology. After 2000, mathematics in schools was profoundly affected by school reforms, especially the introduction of new frameworks, in particular the school educational programmes, the establishment of the state school-leaving exam, which incorporated mathematics as a compulsory school-leaving exam subject for certain types of schools, and the introduction of individual entrance exams at secondary schools. Based upon a qualitative analysis of curricular documents, maths textbooks and studies of the specialist literature, this article examines not only the causes and effects of the aforementioned changes over the course of these years, but also considers the current status of the subject and its developing trends.